The Evaluation of Cloud Feedback at Local Scale either Cooling or Warming - Malek, Esmaiel (Current Approaches in Science and Technology Research Vol. 3, 2021)
Clouds influence the climate through both positive and negative feedback. To study these effects at local scale, a radiation station was set up, which used two CM21 Kipp & Zonen pyranometers (one inverted), and two CG1 Kipp & Zonen pyrgeometers (one inverted) in Logan, Utah, USA. Four CV2 Kipp & Zonen ventilation systems were used to ventilate the pyranometers and pyrgeometers. The ventilation of pyranometers and pyrgeometers prevent dew, frost and snow accumulation, which would otherwise disrupt the measurement. Knowing that available energy (Rn) as Rn = Rsi ? Rso + Rli ? Rlo where Rsi and Rso are downward and upward solar radiation, respectively, and Rli and Rlo as atmospheric and terrestrial, respectively, on a daily and annual basis, the consequences of cloudiness were assessed. The findings indicate that for the partly cloudy days of 4 and 5 September, 2007, cloudiness caused less available energy (Rn) in the amounts of -1.83 MJ·m-2·d-1 and -3.83 MJ·m-2·d-1 on these days, respectively. Because of the cloudiness at the experimental site, as illustrated,, the net radiation loss was 2,804 ? 4,055 = -1,251 MJ·m-2·y-1, As a result of the cloudiness, this implies a negative feedback.